2020
DOI: 10.1016/j.ast.2019.105637
|View full text |Cite
|
Sign up to set email alerts
|

Noise reduction of a Counter Rotating Open Rotor through a locked blade row

Abstract: Counter Rotating Open Rotors (CROR) have the potential to significantly reduce aircraft emissions. However, there are a number of concerns surrounding their noise levels. In this contribution, we propose a number of novel configurations to reduce the noise of CROR for general aviation aircraft. In particular, we lock either fore or aft blade row on departure and approach, and keep the CROR trimmed at the same thrust as in design configuration (both rotors running). The CROR is switched back to design configura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 34 publications
1
8
0
Order By: Relevance
“…For subsequent indices, the amplitudes of the fore rotor are generally greater than those of the aft rotor. This highlights the significance of the upstream interactions and agrees with previous findings on the importance of the potential interactions for low-solidity design CROR [6,7,20,57].…”
Section: Aerodynamic Analysissupporting
confidence: 91%
See 1 more Smart Citation
“…For subsequent indices, the amplitudes of the fore rotor are generally greater than those of the aft rotor. This highlights the significance of the upstream interactions and agrees with previous findings on the importance of the potential interactions for low-solidity design CROR [6,7,20,57].…”
Section: Aerodynamic Analysissupporting
confidence: 91%
“…Both studies showed that the CROR follows the same relationship as the isolated rotor where lower tip speeds and larger blade counts are favourable for reduced noise. Smith et al [20] performed a parametric study of the effect of the blade count when either fore or aft blade row was locked to reduce noise. Whilst the authors demonstrated that the noise could be reduced through locking a blade row, ultimately the lowest noise was found for a CROR with the greatest blade count combination.…”
Section: Introductionmentioning
confidence: 99%
“…In the present work, the far-field acoustics is efficiently calculated using the FW-H equation [28], following the Farassat Formulation 1A [29], taking as input CFD solutions of the surface pressure fields. The formulation has been widely used for far-field noise predictions of aircraft, wind turbines [30], and coaxial propellers [ 31]. The Farassat Formulation 1A [29] solves surface terms of the FW-H equation, i.e.…”
Section: Far-field Acoustic Calculationmentioning
confidence: 99%
“…The potential performance benefits of a CROR relative to single propeller engines and conventional turbofans have been extensively discussed in the literature, from acoustic [11]- [19], aerodynamic [11], [15], [20]- [23] and operability [13], [20]…”
Section: Introductionmentioning
confidence: 99%